Pengaruh Store Atmosphere dan Kualitas Layanan Terhadap Keputusan Pembelian Konsumen pada Mari Kopi di Kabupaten Jeneponto - Afrilla Razky Maharani Sukimin; Muhammad Ichwan Musa; Annisa Paramaswary Aslam; Muh. Yushar Mustafa; Achmad Ridha (SINOMIKA JOURNAL: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2026)
The growth of the coffee shop business has intensified competition among local café operators, including Mari Kopi in Jeneponto Regency. Consumers no longer consider only product and price; they also weigh the establishment's atmosphere and the service experience provided. This study aims to analyze the influence of store atmosphere and service quality on consumer purchasing decisions at Mari Kopi in Jeneponto Regency. An explanatory quantitative approach with a survey design was employed. Data were collected via questionnaires distributed to 150 consumers selected through purposive sampling. Data analysis techniques included descriptive analysis, validity and reliability testing, classical assumption testing, multiple linear regression, t-tests, F-tests, and the coefficient of determination. The results indicate that store atmosphere has a positive and significant effect on consumer purchasing decisions. Service quality also positively and significantly influences purchasing decisions, contributing more dominantly than store atmosphere. Simultaneously, store atmosphere and service quality significantly affect consumer purchasing decisions, with an R-square value of 0.829. This indicates that 82.9% of the variation in purchasing decisions can be explained by these two variables, while the remaining 17.1% is influenced by factors outside the research model. These findings imply that Mari Kopi needs to enhance its physical atmosphere, service speed, staff responsiveness, and overall consumer experience to strengthen purchasing decisions.